Some Static Spherically Symmetric Perfect Fluid Distribution with Spin: Solutions and Physical Parameters of Static Fluid Spheres (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present paper provides solution of E-C field equations for static fluid sphere by a suitable choice of metric potential in three different cases. Various physical parameters have been found and constants appearing in solution have been fixed using boundary conditions.